Politics in History: The Chilean radical right in the 20th century - Sznajder, Mario (Araucaria, 2015)
This work characterizes an important aspect of the political culture of the Chilean radical right in the 20th century: its use of history as a political tool and the introduction of political themes into the presentation of historical subjects or events. The main example is the reliance on the work of Diego Portales and his foundational role in the formation of the Chilean state and its institutions. The analysis describes the development of a Chilean radical right which ideologically relies on the work of serious historians but also “uses” history for contemporary political purposes. The period analyzed is the 20th century in which Chile alternated between democracy and authoritarian dictatorships which were in a certain way influenced also by the radical right.